The Consequences of Mechanical Vibration Exposure on the Lower Back of Bus Drivers: A Systematic Review - Hyago Gabriel Oliveira Mendes; Bianca de Moraes Tomaz; Ana Carolina Coelho-Oliveira; Juliana Pessanha de Freitas; Márcia Cristina Moura-Fernandes; Marco Antônio de Souza-Gama; Francisco José Salustiano da Silva; Arlete Francisca-Santos; Luiz Felipe Ferreira-Souza; Aderito Seixas; Redha Taiar; Mario Bernardo-Filho; et al. (Applied Sciences, 2021)
Professional drivers are exposed to whole-body vibration while driving, which contributes to an increased risk of developing physical problems, such as pain in the lower back. This article aims to review the effects of vibration exposure on bus drivers. Searches were performed on the PubMed, Embase, Web of Science, and Scopus databases. Only full articles of observational and experimental studies that investigated the effects of vibration on bus drivers with consequences in the lumbar region published in English were included. Data on driver demographics, study design, objectives, bus model, seat model, length of exposure to vibration, and outcomes were extracted. Two studies were classified as evidence level III-2 and three studies as level III-3. The methodological quality of the publications presented one with a moderate and four with a serious risk of bias. In all the publications, pain in the lumbar spine was reported. In conclusion, the results of this systematic review suggest that bus drivers are exposed to mechanical vibration in their work routine, and this might be considered a risk factor for the development of pain in the lumbar spine, bearing in mind that the exposure is for long periods.